Categorical Exclusions: Exploring Legal Responses to Health Care Discrimination Against Transsexuals - Hong, Kari I. (Columbia Journal of Gender and Law, 2002)
Health insurance has an enormous impact on determining who receives medical care. If a policy does not cover a particular treatment, an individual in need of care either pays for the medical procedure from her own resources or foregoes treatment altogether. When a person’s income, rather than her established medical need, determines the quantity and quality of care she receives, society is confronted with troubling ethical questions of what type of medical delivery system it provides for its citizens. Although this is an important inquiry, I begin this article by focusing on another disquieting aspect of health care access: How does the legal system respond to private insurers that do not cover treatments because of their dislike of a patient or their hostility toward a patient’s condition? To date, the federal government has initiated two sweeping measures to protect patients who are denied health care for improper reasons. In 1965 Congress enacted the Medicaid Act to provide minimal medical care to lower-income individuals. One of its most important components prevents state legislatures from refusing treatment or reducing payment for a targeted or singled-out medically necessary condition. When a Medicaid recipient believes she is being unfairly denied medical treatment, she can turn to the federal courts to ensure that a state legislature’s coverage of health conditions is based on proper medical and fiscal criteria.